(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
This field study was conducted at the Sugarcane ResearchCentre at Guneid (latitude 150 N, longitude 330E) for two consecutiveseasons (2007/08 and 2008/09). The objective was to evaluate andvalidate the suitability of a new improved field evaluation method (IFEM)in comparison to the conventional field evaluation method (CFEM) whichis widely used by pathologists worldwide in identifying resistantsugarcane genotypes to the smut disease. Nine sugarcane genotypes weretested, and sugarcane varieties CO 527, CO 997 and CO 6806 were usedas checks. These experimental materials were inoculated artificially bytwo methods viz: i) Dip method (DM) and ii) Taiwanese pin-prickmethod (TPPM). Smut resistance evaluations by the new improved 8-6-6field evaluation method, which took 20 months, identified 10 genotypesas highly resistant (HR) or resistant (R) using TPPM and 12 genotypes asHR or R using DM. The conventional 12-12-12 method (CFEM), whichrequires 36 months to complete, identified 9 genotypes as HR or R usingTPPM and 10 genotypes as HR or R using DM. Differences betweenCFEM and IFEM were not significant in both DM and TPPM. Therefore,IFEM can be used confidently for routine evaluations of sugarcanegermplasm as an alternative to CFEM, to efficiently save time and land.